Can Company Size Moderate Good Corporate Governance on Disclosure of Sustainability Reports? Apakah Ukuran Perusahaan Dapat Memoderasi Good Corporate Governance Terhadap Pengungkapan Sustainability Report? - Biduri, Sarwenda; Nur Fadhila, Shafira; Rahma Dewi, Santi; Maryanti, Eny (Journal of Accounting Science, 2023)
This research was carried out with the aim of testing Good Corporate Governance on Disclosure of Sustainability Reports with Company Size as Moderation. Good Corporate used in this study is using Independent Commissioners, Audit Committee, Board of Directors and Managerial Ownership. Disclosure of the Sustainability Report that is disclosed is Economic, Social and Environmental. The size of the company uses the Logarithm of Natural Assets (LN Assets). This type of research used is quantitative research. The population of this study are state-owned companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The sample selection used was the purposive sampling method from 56 registered state-owned companies and based on the available criteria, the number of samples was 9 companies that met the criteria. Documentation techniques are used as data collection, outer model analysis and inner model are data analysis used for this study using the smartPLS 3.2.7 application. The results of the research that has been conducted show that (1) the Independent Commissioner has influence over the disclosure of the Sustainability Report, (2) the Audit Committee has influence over the disclosure of the Sustainability Report, (3) the board of directors has influence over the disclosure of the Sustainability Report, (4) Managerial ownership has an influence on the disclosure of the Sustainability Report, (5) Company size cannot moderate the influence of independent commissioners on the disclosure of the Sustainability Report, (6) Company size cannot moderate the influence of the audit committee on the disclosure of the Sustainability Report, (7) Company size cannot moderate the influence of the board of directors on the disclosure of the Sustainability Report, (8) Company size cannot moderate the effect of managerial ownership on the disclosure of the Sustainability Report. The implications of this research are from previous research examining GCG on disclosure of sustainability reports, the results are still inconsistent.